The encyclopedia of jazz - Feather, Leonard G. (Da Capo Press, 1960)
With more than 2,000 biographies and 200 photos, the first paperback publication of this acclaimed reference spans the history of jazz from its origins to 1959. The book also features essays on the jazz tradition, its major players and composers, the relationship between jazz and classical music, a social history of jazz in America, and more.